Implicit Unstructured-Mesh Method for Calculating Poiseuille Flows of Rarefied Gas (Communications in Computational Physics, 2010)
An implicit high-order accurate method for solving model kinetic equationsis proposed. The method is an extension of earlier work on the construction of an explicitTVD method for hybrid unstructured meshes in physical space and is illustratedon the Poiseuille flow of rarefied gas. Examples of calculations are provided for differentKnudsen numbers and mesh resolutions, which illustrate the efficiency and highaccuracy of the new scheme.